2022
DOI: 10.1155/2022/6007698
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative Analysis of Efficacy and Prognosis of Hemodialysis and Peritoneal Dialysis for End-Stage Renal Disease: A Meta-analysis

Abstract: Objective. This meta-analysis is aimed at systematically assessing the efficacy and prognosis of hemodialysis (HD) and peritoneal dialysis (PD) in the treatment of end-stage renal disease (ESRD). Methods. China National Knowledge Infrastructure, VIP, SinoMed, Cochrane Library, PubMed, and Embase databases were searched for relevant studies to evaluate the two different dialysis methods for ESRD. The search time was set from 2010 to 2021. Meta-analysis was performed using Stata16.0. The treatment group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The survival rate of patients with renal function is higher than that of 5 Computational and Mathematical Methods in Medicine patients without renal function, and the quality of life of patients with renal function is better than that of patients without renal function. Because of the different dialysis characteristics of HD and PD, some studies have shown that PD can protect patients' renal function better than HD [52,53]. In PD patients, the loss of renal function can be slowed down by using renin-angiotensin-aldosterone system blockers and diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…The survival rate of patients with renal function is higher than that of 5 Computational and Mathematical Methods in Medicine patients without renal function, and the quality of life of patients with renal function is better than that of patients without renal function. Because of the different dialysis characteristics of HD and PD, some studies have shown that PD can protect patients' renal function better than HD [52,53]. In PD patients, the loss of renal function can be slowed down by using renin-angiotensin-aldosterone system blockers and diuretics.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we observed that patients switching to HD preoperatively had a significantly lower postoperative BUN and SCr levels. This could be explained by a major difference in dialysis principles between PD and HD: HD is more effective in removing small molecules and water while PD is better capable at the removal of middle molecular substances (19). In spite of that, patients in the preoperative HD group seemed to have a higher proportion of postoperative complications than patients in the preoperative PD group, especially a higher incidence of hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Studies have shown that the incidence of malnutrition in long-term peritoneal dialysis patients is over 70%, and malnutrition directly affects the prognosis and survival of patients on dialysis. 15,16 Because of the high prevalence of coexisting problems in peritoneal dialysis patients, as well as the fact that each patient is unique, individualised nutrition therapy is essential for such patients. However, there is no uniform implementation standard, and the intervention effect and risk factors remain to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, patients will inevitably lose some nutrients during the process of peritoneal dialysis, resulting in a nutritional imbalance and the subsequent appearance of some symptoms such as malnutrition and abnormal calcium and phosphorus metabolism 12–14 . Studies have shown that the incidence of malnutrition in long‐term peritoneal dialysis patients is over 70%, and malnutrition directly affects the prognosis and survival of patients on dialysis 15,16 . Because of the high prevalence of coexisting problems in peritoneal dialysis patients, as well as the fact that each patient is unique, individualised nutrition therapy is essential for such patients.…”
Section: Discussionmentioning
confidence: 99%